Pengaruh Rasio-Rasio Terhadap Metode Altman Z-Score Dalam Memprediksi Financial Distress Pada Harga Saham Perusahaan Subsektor Perdagangan Ritel - Muhammad Fithrayudi; Kukuh Prayugo; Y Yohani (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
The purpose of this study was to examine and analyze the impact of financial emergencies using the Altman zscore method on the share prices of companies in the retail subsector on the Indonesian Stock Exchange. This study uses an intentional sampling method with an overall sample of 23 companies in the retail subsector. The analysis of this study uses the Eviews 10 program. This study uses 5 independent variables and 1 dependent variable, the dependent variable of this study consists of working capital to total assets (WCTA), retained earnings to total assets (RETA), earnings before interest and Taxes on total assets (EBITTA), market value of equity to book total (MVEBVTL), sales to total assets (STA), while the dependent variable of this investigation is the price of the shares. Based on the results of this study, it is partially determined that (1) WCTA has a significant negative impact on share prices. (2) RETA have no influence on the share price. (3) EBITTA have a positive and decisive effect on the share price. (4) MVEBVTL has a positive and significant influence on share prices and (5) STA have no influence on share prices.Simultaneously all independent variables, namely WCTA, RETA, EBITTA, MVEBVTL, and STA affect the share price when examined together. Keywords: altman z-score, financial distress, insolvency